Comparison Analysis of Gait on Transfemoral Patient using Four-bar Linkage Friction and Pneumatic Swing Phase Control - Cendana Sardiman; Burlian Mughnie; Tri Riana Lestari (Journal Center of Excellent : Health Assistive Technology, 2023)
Various kinds of artificial knee joints continue to develop over time in the prosthetic world, for example, the four-bar linkage friction and four-bar linkage pneumatic. The knee joint mechanism differs between four-bar linkage friction and pneumatic swing phase control, which can affect the transfemoral patient's gait. Artificial knee joints, four-bar linkage friction, and four-bar linkage pneumatic are rarely used in the clinical laboratory of Orthotics and Prosthetics because clinical only provides the simple type of knee joint (manual lock knee). There were 84 transfemoral patients recorded in the clinic laboratory Orthotics Prosthetics Department for this research. None of them ever use these two types of knee joint four-bar linkage knee joints. Four transfemoral amputees were recruited in this research. They were asked to walk comfortably to investigate the gait function with a 10-meter walking test (10 MWT) using two types of the knee joint: four-bar linkage friction and four-bar linkage pneumatic. After that, differences in cadence, step length, and walking speed with two knee joint was tested and analyzed by independent t-test and chi-square. The spatiotemporal gait parameters comparison result between four-bar linkage pneumatic and four-bar linkage friction were: walking speed was 59.2 m/min compared to 54.2 m/min (p-value = 0.000). Cadence was 87.6 step/min compared to 72.5 steps/min (p-value = 0.000), and step length was 1.14 cm compared to 0.96 cm (P-value = 0.000). The gait analysis of the knee joint compare to normal gait showed that the odds ratio (OR) Cadence was 4,2 (p-value = 0.000), Step length was 3,5 (P-value = 0.000), ad walking speed was 4 (p-value = 0.000). There are significantly different spatiotemporal gait parameters between four-bar linkage friction and pneumatic swing phase control. The cadence, step length, and walking speed result from the four-bar linkage pneumatic is closer to mimicking normal gait.